Phenocam - Red Green Blue (RGB) Composite Image Mean Values from Skogaryd Stordalen Catchment, Mast 5.9m Phenocam 01 - Skogaryd Research Catchment (University of Gothenburg, 2022)
Phenocamera RGB composite averaged daily from quality-filtered photos from 10 a.m. to 2 p.m.
Skogaryd Research Catchment (2022). Phenocam - Red Green Blue (RGB) Composite Image Mean Values from Skogaryd Stordalen Catchment, Mast 5.9m Phenocam 01, 2018-01-01–2018-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/m0D6A9OkwUPavGjRCJAulGB6
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap